The Influence of Differentiation Strategy on Competitive Advantage through Product Positioning, Moderated by Competition Intensity: A Study of O Coffee Kandis - Pangaribuan, Siska Devawati; Wono, Hilda Yunita (Dinasti Publisher, 2026)
Increasing competition in the coffee shop industry encourages businesses to develop differentiation strategies that can create competitive advantage. This study aims to analyze the effect of differentiation strategy on competitive advantage through product positioning, as well as to examine the moderating role of competitive intensity at O Coffee Kandis, Siak Regency, Riau. A quantitative approach was employed using a sample of 190 consumer respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results indicate that differentiation strategy has a positive and significant effect on product positioning (β = 0.105; p = 0.025) and competitive advantage (β = 0.121; p = 0.012). Product positioning partially mediates this relationship with a significant indirect effect. Competitive intensity shows a strong direct effect on product positioning (β = 0.777; p < 0.001) but fails to moderate the relationship between differentiation strategy and product positioning (β = 0.047; p = 0.311). The structural model explains R² = 0.64 for product positioning and R² = 0.45 for competitive advantage. These findings contribute to the marketing strategy literature by highlighting the importance of product positioning as a mechanism that bridges differentiation strategies in creating competitive advantage.